Dietary phylloquinone intake and risk of type 2 diabetes in elderly subjects at high risk of cardiovascular disease - Ibarrola-Jurado, Núria; Salas-Salvadó, Jordi; Martínez-González, Miguel A; Bulló, Mònica (The American journal of clinical nutrition, 2012)
Limited evidence from human and animal studies has suggested that vitamin K has a potentially beneficial role in glucose metabolism and insulin resistance. We analyzed the cross-sectional and longitudinal associations between dietary phylloquinone intake and type 2 diabetes in elderly subjects at high cardiovascular risk. Cross-sectional associations were tested in 1925 men and women in the Prevention with the Mediterranean Diet trial. A longitudinal analysis was conducted on 1069 individuals free of diabetes at baseline (median follow-up: 5.5 y). Biochemical and anthropometric variables were obtained yearly. Dietary intake was collected during each annual visit by using a food-frequency questionnaire, and phylloquinone intake was estimated by using the USDA database. The occurrence of type 2 diabetes during follow-up was assessed by using American Diabetes Association criteria. Dietary phylloquinone at baseline was significantly lower in subjects who developed type 2 diabetes during the study. After adjustment for potential confounders, risk of incident diabetes was 17% lower for each additional intake of 100 μg phylloquinone/d. Moreover, subjects who increased their dietary intake of vitamin K during the follow-up had a 51% reduced risk of incident diabetes compared with subjects who decreased or did not change the amount of phylloquinone intake. We conclude that dietary phylloquinone intake is associated with reduced risk of type 2 diabetes. This trial was registered at http://www.controlled-trials.com as ISRCTN35739639.